(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Invasive management of coronary artery disease (CAD), including percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG), improves outcomes in selected patients; however, its utilization in non-metropolitan Indian tertiary centres remains variable. To estimate the proportion of CAD admissions managed invasively at a tertiary centre in Tamil Nadu and to identify independent determinants of the management decision. Materials and Methods: A retrospective hospital-based observational study was conducted among consecutive adult CAD admissions between January 2022 and December 2024. The primary outcome was management modality (invasive vs conservative). A total of 320 patients were included. Bivariate analysis and multivariable logistic regression were performed to identify determinants of invasive management. Results: Of 320 CAD admissions, 110 (34.4%) received invasive management. After multivariable adjustment, STEMI presentation (aOR 4.34, 95% CI 2.48–7.58; p<0.001), prior revascularization (aOR 3.93, 95% CI 1.60–9.66; p=0.003), age <65 years (aOR 2.13 vs ≥65; p=0.018), higher socio-economic status (BG Prasad I–III vs IV/V, aOR 2.27; p=0.002), and residence within 50 km to the tertiary care (aOR 2.04; p=0.015) independently increased the odds of invasive management. Conclusion: In the present study, clinical severity (STEMI), prior cardiac history, younger age, higher SES, and geographic proximity emerged as the dominant independent determinants of invasive CAD management. These findings identify intervention targets for narrowing the gap between guideline-directed and delivered invasive care in mixed urban-rural districts.